Protective Effect of Danshen Zexie Decoction Against Non-Alcoholic Fatty Liver Disease Through Inhibition of ROS/NLRP3/IL-1β Pathway by Nrf2 Signaling Activation - Biao, Yaning; Chen, Jian; Liu, Chenxu; Wang, Ruilong; Han, Xue; Li, Li; Zhang, Yixin (Frontiers in Pharmacology, 2022)
Lipid metabolism disorders are a prominent characteristic in the pathological development of non-alcoholic fatty liver disease (NAFLD). Danshen zexie decoction (DZD) is a Chinese herbal medicine that is based on zexie decoction and has an effect of regulating lipid mechanism. However, the anti-NAFLD effect and mechanism of DZD remain unclear. In this study, we observed the therapeutic effect of DZD on NAFLD rats and investigated its possible mechanisms. Sixty SD rats were randomly assigned to six groups: a control group, model group, Yishanfu (polyene phosphatidylcholine) group, and low, middle and high-dose DZD groups. High-fat diet (HFD) was fed to the rats to establish an NAFLD model, and each treatment group was given corresponding drugs at the same time for eight consecutive weeks. The results revealed that the obvious lipid metabolism disorder and liver injury induced by HFD were alleviated by treatment with DZD, which was verified by decreased serum TC, TG, ALT, AST, liver TC, TG, and FFA, as well as the alleviation of hepatic steatosis. The production of ROS in the rats was reduced after treatment with DZD. The SOD and GSH activities were increased with DZD treatment, while the MDA level was decreased. The administration of DZD could decrease serum IL-1β and IL-18 contents. Moreover, DZD upregulated the expressions of Nrf2, HO-1, GCLC, and GCLM, while it suppressed the expressions of NLRP3, caspase-1, GSDMD, and GSDMD-N. In conclusion, the data show that DZD reduced lipid accumulation, alleviated oxidative stress and inflammation, and inhibited pyroptosis in NAFLD rats, which might be ascribed to suppression of the ROS/NLRP3/IL-1β signaling pathway by activation of Nrf2. Overall, these results indicate that DZD is expected to be a therapeutic drug for NAFLD.